Growth of hierarchical TiO2 flower-like microspheres/oriented nanosheet arrays on a titanium mesh for flexible dye-sensitized solar cells. Issue 40 (25th September 2018) - Xu, Yuanmei; Li, Xueshi; Xiao, Ming; Xiong, Xiaoming
Abstract : A triple-layer TiO2 (TiO2 -TL) structure was synthesized with an over-layer composed of TiO2 flower-like microspheres (MSs), a middle layer of nanosheet arrays (NSAs) and an under-layer of compact film (CF) on a titanium (Ti) mesh substrate using a one-step hydrothermal route and used to make a series of flexible dye-sensitized solar cells (DSSCs). Abstract : A triple-layer TiO2 (TiO2 -TL) structure was synthesized with an over-layer composed of TiO2 flower-like microspheres (MSs), a middle layer of TiO2 nanosheet arrays (NSAs) and an under-layer of TiO2 compact film (CF) on a flexible titanium (Ti) mesh substrate using a one-step hydrothermal route followed by calcination post-treatment and used to make a series of flexible dye-sensitized solar cells (DSSCs). The dependence of the physical features (diameter and length) of this hierarchical TiO2 structure on the NaOH concentration, temperature and hydrothermal duration is systematically studied. The fully flexible DSSCs employing such a hierarchical triple-layer TiO2 structure as a photoanode and poly-aniline film (PANI) on the indium doped tin oxide/polyethylene naphthalate (ITO/PEN) substrate as a counter electrode exhibited a power conversion efficiency of 5.04%, which mainly benefited from the enhanced capacity for effective light scattering of MSs and fast charge transfer of NSAs.